2017
DOI: 10.1093/neuonc/nox076
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of a novel PAK4 locus influences ototoxicity susceptibility following cisplatin and radiation therapy for pediatric embryonal tumors

Abstract: We identified and replicated a novel CpG methylation loci (cg14010619) associated with ototoxicity severity. Methylation at cg14010619 may modify PAK4 activity, which has been implicated in cisplatin resistance in malignant cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…From the 30 included papers, 44% were retrospective with a sample size ranging from 39 to 317 (Table 1). Some of them (33%) were performed on patients younger than 25 years of age 30,3747 and 80% on both genders. The ethnicity was rather broad with Northern America and Norwegians representing together the majority of the articles (14%) 31,41,4850 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 30 included papers, 44% were retrospective with a sample size ranging from 39 to 317 (Table 1). Some of them (33%) were performed on patients younger than 25 years of age 30,3747 and 80% on both genders. The ethnicity was rather broad with Northern America and Norwegians representing together the majority of the articles (14%) 31,41,4850 .…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three percent of the studies were performed on osteosarcoma 32,3740,4244,46,47,51,5660 , medulloblastoma in 33% 30,32,3841,4446,56 , while testicular cancer was studied in 17% of them 31,33,4850,53 . How the dose was reported varied between the studies with 17 studies reporting median values of cisplatin administration (from 100 to 525.5 mg/m 2 ) 30,31,36,4244,4750,52,5459 , and reporting mean values (from 328.2 to 425.5 mg/m 2 ) 32,38,39,45 . Seven studies only reported the range 33,37,40,46,51,53,60 , and 3 the dose per cycle 41,60,61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from genetic factors, epigenetic factors influencing cisplatin ototoxicity have recently come to attention. In a pediatric medulloblastoma and primitive neuroectodermal tumor patient cohort, Brown et al (2017) found an association between increased cisplatin ototoxicity susceptibility and a methylation locus (cg14010619) in the P21 (RAC1) Activated Kinase 4 (PAK4 gene). This gene is responsible for stereociliary bundle migration in inner and outer cochlear hair cells.…”
Section: Ototoxicitymentioning
confidence: 98%
“…While it is ideal to collect samples prior to the time of diagnosis, ongoing assessments are evaluating if there are metastable epialleles related to pediatric cancer that can evaluated with samples collected at the time of diagnosis. [ 57 ] Because DNA methylation is tissue specific and is influenced by both genetic variation and environmental factors, alterations in DNA methylation may also provide mechanistic insight into treatment response and survivorship, as have been reported, [ 58,59 ] to improve clinical outcomes through epigenetic therapies in children with cancer. As noted, while a few studies have utilized DBS for epigenome‐wide assessments, to our knowledge, there have been no assessment exploring the utility of primary teeth to evaluate DNA methylation patterns, providing territory for novel explorations of pediatric cancer risk.…”
Section: Novel or Underutilized Molecular Approaches For Assessing Exposures In Environmental Studies Of Pediatric Cancermentioning
confidence: 99%